Explanation for the signs and symptoms of tooth eruption: mast cells - Solange de Oliveira Braga Franzolin; Maria Inês Moura Campos Pardini; Leda A. Francischone; Elenice Deffune; Alberto Consolaro (Dental Press Editora, 2019)
Abstract This study contributes to the understanding of the mechanisms associated with signs and symptoms of tooth eruption, by investigating the presence of mast cells in pericoronal tissues during the intraosseous (Group 1) and submucosal (Group 2) phases of eruption. We compared findings for these two groups with each other and with those for the oral mucosa (Group 3). In each group, 14 specimens were analyzed microscopically after hematoxylin and eosin staining and immunohistochemical analysis of c-Kit and tryptase expression. Results revealed that the number and density of mast cells is different in follicular tissues according to the eruption phase, which may mean that: 1) masticatory trauma of the oral mucosa and dental follicles in the submucosa may explain why reduced enamel epithelium exposes enamel to the cells of the connective tissue; 2) exposure of antigenic enamel proteins might correspond to the release of sequestered antigens, which may lead to the interaction of IgE and a greater number of mast cells in the region; and 3) the consequent degranulation and the local release of mediators, such as histamine, leukotrienes, prostaglandins, proteases, cytokines and growth factors, contribute to the understanding of signs and symptoms associated with tooth eruption.